PENGARUH TAMBAHAN PENGHASILAN DAN KOMITMEN ORGANISASIONAL TERHADAP SEMANGAT KERJA APARATUR SIPIL NEGARAPADA DINAS PENGENDALIAN PENDUDUK, KB, KEPENDUDUKAN DAN PENCATATAN SIPIL PROVINSI SUMATERA BARAT - Henny Sjafitri; Ramadhania Ramadhania; Meugah Fauziah (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2020)
The purpose of this study is to investigate and analyze the effect of additional income and organizational commitment on the morale of the state civil apparatus in the Population Control Office, Family Planning, Population and Civil Registry of West Sumatra Province. The research method used is descriptive quantitative. The population in this study amounted to 51 and the sample in this study amounted to 51 respondents. While the data analysis technique used in this study is the t test, F test and the coefficient of determination. The results of the study show that additional income (X1) and organizational commitment (X2) together affect work morale. This can be seen from the value of F_count> F_table or 26.836> 3.06 and a significant level = 0.000